Web-based tools for the interpretation of chain-like protein Spot patterns on two-dimensional gels - Maurer, Martin H. (Current proteomics, 2012)
Two-dimensional gel electrophoresis is a standard tool of proteomic analysis, consisting of first dimensional protein separation according to the respectiv...